2013
DOI: 10.1089/ars.2012.4586
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Studies of a New Nrf2 Partner IQGAP1: A Critical Role in the Stability and Transactivation of Nrf2

Abstract: IQGAP1 may play a critical role in the stability and transactivation of Nrf2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 58 publications
(50 reference statements)
3
38
0
Order By: Relevance
“…More recent studies have revealed that IQGAP1 regulates nuclear translocation and transcriptional activation of both nuclear factor-erythroid-related factor 2 (Nrf2) (39) and Dishevelled (40). Analogous to our observations with ER␣ transcriptional activation, knockdown of IQGAP1 impairs the transcriptional activation of target genes by Nrf2 and Dishevelled (39,40). By contrast, CD8 ϩ T cells isolated from IQGAP1-deficient mice exhibit increased expression of interferon-␥, an established target gene of NFAT (38).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…More recent studies have revealed that IQGAP1 regulates nuclear translocation and transcriptional activation of both nuclear factor-erythroid-related factor 2 (Nrf2) (39) and Dishevelled (40). Analogous to our observations with ER␣ transcriptional activation, knockdown of IQGAP1 impairs the transcriptional activation of target genes by Nrf2 and Dishevelled (39,40). By contrast, CD8 ϩ T cells isolated from IQGAP1-deficient mice exhibit increased expression of interferon-␥, an established target gene of NFAT (38).…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, IQGAP1 regulates the nuclear translocation of nuclear factor of activated T cells (NFAT) and alters transcription of NFAT target genes (38). More recent studies have revealed that IQGAP1 regulates nuclear translocation and transcriptional activation of both nuclear factor-erythroid-related factor 2 (Nrf2) (39) and Dishevelled (40). Analogous to our observations with ER␣ transcriptional activation, knockdown of IQGAP1 impairs the transcriptional activation of target genes by Nrf2 and Dishevelled (39,40).…”
Section: Discussionsupporting
confidence: 84%
“…Some nuclear functions of IQGAP1 are elicited via direct interaction with and regulation of transcription factors, such as estrogen receptor ␣ (ER␣) and nuclear factor erythroid-related factor 2 (19,20). In addition, IQGAP1 binds to ␤-catenin and enhances its nuclear accumulation and transcriptional co-activation (21).…”
mentioning
confidence: 99%
“…We have recently identified IQGAP1 (IQ motif-containing GTPase-activating protein 1) as a novel binding partner of Nrf2 (14). Like other IQGAP family proteins such as IQGAP2 and IQGAP3, IQGAP1 shares conserved protein structure, including calmodulin-binding IQ motifs and the GTPase-activating protein homology domain (15).…”
mentioning
confidence: 99%